Microcephaly and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The prevalence of epilepsy and learning disability among various types of microcephaly was determined in a study of 66 cases (age range from 2 to 19 years) at the National Research Centre, Cairo, Egypt, and the Department of Human Genetics and Teratology, National Center for Epidemiology, Budapest, Hungary.